Enhancing Security and Oversight with Public Meeting Monitoring Drone - T Chandra Sekhar Rao; S Divya; M Vennela; S Kavya; S Anil Yadav; R Yashoda (International Journal of Scientific Research in Science and Technology, 2024)
This paper proposes the utilization of drones equipped with advanced surveillance capabilities to enhance security measures and oversight during public meetings. The drone's ability to capture real-time video footage and provide aerial reconnaissance enables authorities to detect potential threats, crowd disturbances, and unauthorized activities with greater efficiency and accuracy. This drones are equipped with a variety of sensors, including cameras, LiDAR, thermal imaging, and obstacle detection systems. These sensors provide the drone with environmental awareness, allowing it to detect and avoid obstacles, maintain stable flight, and capture high resolution data. Motors and propellers are wired. These components determined space available for the electronics as well as decide the weight that can be kept on the helicopter and still have to lift. A sensor board called the IMU Shield is interfaced. This board included all of the major sensors that is needed to achieve flight which are needed to work together to make sure the Quadcopter maintains stable flight while moving or hovering. Finally a Lithium-ion polymer (Lipo) battery is purchased because they have the best ratio of weight to power. The quadcopter is made to move in desired direction with the help of Electronic Speed Control (ESC). As you can see, drones are becoming increasingly popular in education and on college campuses. By embracing drones, educators can provide students with valuable skills and prepare them for the future and keep them safe in the present. While concerns regarding privacy, safety, and regulation persist, the potential benefits of these autonomous aerial platforms continue to drive research and development efforts, making them a transformative force in modern industries and society.By leveraging drone technology, stakeholders can proactively mitigate security risks, safeguard public safety, and ensure adherence to regulations, thereby fostering a more secure and transparent environment for public gatherings.
Keywords: Security Enhancement; Public Meeting Monitoring; Drone Surveillance; Real-time Monitoring; Crowd Surveillance